1999
DOI: 10.1046/j.1440-1746.1999.02027.x
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of increased risk of colorectal cancer in individuals heterozygous for the Cys282Tyr haemochromatosis mutation

Abstract: Heterozygosity for the Cys282Tyr mutation of HFE does not appear to be a risk factor for colorectal carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 17 publications
2
21
0
2
Order By: Relevance
“…When HFE mutations were considered separately, there was only a small, nonsignificant increased risk of colorectal cancer; in this respect therefore, our data support the earlier, negative findings (15,17,18). Our study also considered the colorectal cancer risk to an individual carrying both C282Y and H63D compound heterozygous mutations.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…When HFE mutations were considered separately, there was only a small, nonsignificant increased risk of colorectal cancer; in this respect therefore, our data support the earlier, negative findings (15,17,18). Our study also considered the colorectal cancer risk to an individual carrying both C282Y and H63D compound heterozygous mutations.…”
Section: Discussionsupporting
confidence: 89%
“…Other studies have found no link between any HFE mutation and risk of colorectal cancer. For example, Beckman et al (15) reported that genetic variants of HFE were not associated with increased risk of this disease or of multiple myeloma and breast cancer; two other studies found that heterozygosity for the C282Y mutation did not increase risk of colorectal cancer (17,18). Hence, it would seem that the higher overall statistically significant risk reported by Shaheen et al (19) may be a consequence of inclusion of the African American subjects in their study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterozygous HFE carriership is associated with moderately increased iron parameters, and therefore, it has been suggested to be a genetic modifier of several clonal disorders (solid tumors and hematologic malignancies). Previous association studies regarding common HFE genetic variants in relation with susceptibility for solid tumors such as colon cancer (7,8,(14)(15)(16)(17), or breast cancer (9)(10)(11)18), are rather conflicting. HFE associations were investigated in hematologic malignancies as well.…”
Section: Discussionmentioning
confidence: 99%
“…The S142G variant of TFR was reported to influence cancer susceptibility (colon, breast, myeloma) in combination with distinct HFE genotypes (13). The effects of iron homeostasis, and HFE and TFR genotypes were extensively studied in several solid tumors even in large patient cohorts (7)(8)(9)(10)(11)(12)(14)(15)(16)(17)(18)), but only a few studies with small patient cohorts tested the potential role of HFE in chronic myeloproliferative disorders (CMPD), a clonal disorder of the main iron using tissue of the body (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%